Determinants of Hydration Status in Martial Athletes at The Student Sports Training Center Jakarta - Permatasari, Indah Dwi; Kuswari, Mury; Gifari, Nazhif; Sitoayu, Laras; Mulyani, Erry Yudhya (Nutrition Study Program, Faculty of Medicine, Universitas Negeri Semarang, Indonesia, 2023)
Adolescent athletes are a group that’s vulnerable to decreased water content and has a higher risk of dehydration. Results showed, 22% of adolescent athletes were highly dehydrated. This study aims to knowing the determinants factor of hydration status for martial arts athletes in Pusat Pelatihan Olahraga Pelajar DKI Jakarta. The research uses a quantitive method with a cross sectional design and sample of 50 martial arts athletes (13-18 years). Data obtained through food recall 1x24 hours for fluid consumption, nutritional status with BMI/U, percent body fat with Ultrasonic Body Fat Analyzer SR-HW 05 Serenity instrument, physical activity with PAL sheets, and hydration status with Specific Gravity values. Data analysis using Pearson correlation test. The results showed a significant correlation between female nutritional status (p<0.05), male and female fluid consumption (p<0.05) with hydration status of martial arts athletes. However, there was no significant correlation between male nutritional status, male and female percent body fat, male and female physical activity with hydration status of martial arts athletes (p>0.05). Fluid consumption is factor that affects the hydration status of male and female martial arts athletes. It’s important for athletes to maintain their hydration status in order to carry out training and competitions optimally.